Determinants of cervical cancer screening utilisation among women in the least developed countries: A systematic review and meta-analysis - Tika Rana; Dorothy Ngo Sheung Chan; Bernard Man Hin Law; Kai Chow Choi; Sunil Shrestha; Winnie Kwok Wei So (PLoS ONE, 2025)
Background and aims Globally, cervical cancer is the fourth most common cancer among women, and more than 90% of all cervical cancer-related deaths worldwide are recorded in resource-limited countries. The present review investigated the uptake rate of cervical cancer screening and identified the factors associated with screening service utilisation in the female populations of least developed countries (LDCs). Methods Five electronic databases (EMBASE, Ovid MEDLINE, CINAHL, Cochrane Library, and PubMed) and grey literature were searched for relevant literature using the keywords of the included studies. Both qualitative and quantitative studies were included. Three reviewers performed critical appraisals using the Mixed Methods Appraisal Tool. Meta-analysis was performed to pool the quantitative results from comparable studies. Results A total of twenty-five studies were included in the review. The cervical cancer screening uptake rate in LDCs ranged from 4% to 21%. Multiple factors were associated with screening service utilisation among women in the LDCs, namely socio-demographic characteristics, including employment status (odds ratio (OR): 2.72; 95% CI: 1.97–3.76; p < 0.001); knowledge of cervical cancer and its screening (OR: 3.39; 95% CI: 2.00–5.75; p < 0.001); sexual and reproductive health-related factors such as parity status (OR: 2.73; 95% CI: 1.61–4.64; p = 0.002); healthcare providers’ recommendations (OR: 5.32; 95% CI: 2.44–11.58; p < 0.001); perceived risk of developing cervical cancer (OR: 3.76; 95% CI: 2.62–5.38; p < 0.001); use of media for cervical cancer screening promotion, including radio; cultural factors; and myths and misconceptions about cervical cancer and its screening. Conclusions The uptake of cervical cancer screening among eligible women in the LDCs was notably low. The governments of these countries are advised to invest and allocate additional resources to advance policies and develop cervical cancer prevention programmes that are accessible, affordable, and acceptable.